Pengembangan Model Pendidikan Kesehatan Berbasis Kader Dan Media Digital Dalam Meningkatkan Respon Cepat Masyarakat Terhadap Stroke Akut: Development of a Community Health Education Model Based on Community Health Volunteers and Digital Media to Improve Rapid Community Response to Acute Stroke - Ernawati, Ernawati; Ariani, Sri Purwanti; Nadia, Nur (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Acute stroke is a medical emergency that requires prompt recognition and immediate management to reduce disability and mortality. However, limited public awareness of stroke signs and symptoms, as well as inadequate initial response, remain major causes of delayed treatment at the community level. This study aimed to develop a community health education model based on health cadres and digital media to improve the community's rapid response to acute stroke. This study employed a Research and Development (R&D) design consisting of needs assessment, model development, expert validation, and limited field testing. The study involved health cadres and community members in Kelayan Village selected through purposive sampling. The study variables included model feasibility, community knowledge, and rapid response to acute stroke. Data were collected using validated and reliable questionnaires and observation checklists and were analyzed descriptively. The findings demonstrated that the developed health education model was considered feasible by experts and effectively improved community knowledge regarding the recognition of acute stroke signs and symptoms. In addition, the model enhanced the community's ability to provide an appropriate and timely initial response to suspected acute stroke events compared with the pre-intervention condition. In conclusion, the health cadre- and digital media-based health education model is a feasible and promising innovation for improving community preparedness and rapid response to acute stroke. This model may serve as an alternative community-based health promotion strategy to support early stroke recognition and facilitate timely treatment.